2007
DOI: 10.3892/or.18.6.1489
|View full text |Cite
|
Sign up to set email alerts
|

Identification of molecular targets in head and neck squamous cell carcinomas based on genome-wide gene expression profiling

Abstract: Abstract. DNA amplifications activate oncogenes and are hallmarks of nearly all advanced cancers including head and neck squamous cell carcinoma (HNSCC). Some oncogenes show both DNA copy number gain and mRNA overexpression. Chromosomal comparative genomic hybridization and oligonucleotide microarrays were used to examine 8 HNSCC cell lines and a plot of gene expression levels relative to their position on the chromosome was produced. Three highly up-regulated genes, NT5C3, ANLN and INHBA, were identified on c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
32
0
4

Year Published

2008
2008
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(38 citation statements)
references
References 6 publications
2
32
0
4
Order By: Relevance
“…Putative target genes in HNSCC were identified after direct integration of chromosome alteration and gene expression data, using bioinformatics analysis to specifically identify those gene expression change events associated with copy number alterations (Jarvinen et al, 2006). Our previous work also suggested that the identification of affected genes in chromosomal alteration loci are important to further the understanding of tumorgenesis and progression in SCC (Shimizu et al, 2007;Sugimoto et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Putative target genes in HNSCC were identified after direct integration of chromosome alteration and gene expression data, using bioinformatics analysis to specifically identify those gene expression change events associated with copy number alterations (Jarvinen et al, 2006). Our previous work also suggested that the identification of affected genes in chromosomal alteration loci are important to further the understanding of tumorgenesis and progression in SCC (Shimizu et al, 2007;Sugimoto et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Czerninski et al's findings further support targeting the mTOR pathway as a chemoprevention strategy. Other potential targets for chemoprevention besides mTOR (18) include AKT (14,19,20), cyclooxygenase-2, and EGFR (21,22). The overexpression and activation of these molecules in precancerous lesions and tumors in this mouse model suggests its usefulness for evaluating new drugs that modulate these targets.…”
mentioning
confidence: 99%
“…Numerous studies have focused on identifying the genetic and epigenetic alterations underlying HNSCC (13)(14)(15)(16). Further mutational and genomic analysis of precancerous lesions and tumors induced in the oral-specific mouse model could unveil which lesions are most susceptible to specific chemopreventive agents; for example, whether oral lesions with p53 mutations or cyclin-dependent kinase 2A mutations have enhanced susceptibility to rapamycin.…”
mentioning
confidence: 99%
“…INHBA is a subunit of the complex that inhibits pituitary FSH secretion. Overexpression of INHBA is reported in various cancers including gastric cancer [20,24,25], glioblastoma [26], lung adenocarcinoma [27], esophageal adenocarcinoma [28], tongue squamous cell carcinoma [20], head and neck squamous cell carcinoma [29] and pancreatic adenocarcinoma [30]. Overexpression of INHBA is associated with poor survival in gastric cancer [27], lung adenocarcinoma [27] and head and neck squamous cell carcinomas [29].…”
Section: Inhibin Beta a Is Overexpressed In A Subset Ofmentioning
confidence: 99%